2013
DOI: 10.1111/jpn.12134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dosage and application mode of l‐carnitine on plasma lipid and egg‐yolk cholesterol of turkeys, hatchability of eggs and post‐hatch growth of their offsprings

Abstract: The effect of dosage and application mode of L-carnitine on plasma lipid and egg-yolk cholesterol of breeder turkeys, hatchability of eggs and post-hatch growth response was investigated using 180 breeder hens. The hens were assigned to six dietary treatments in a 2 × 3 factorial arrangements of two application modes of L-carnitine (diet and drinking water) supplemented at 0, 50 and 100 ppm (mg/kg or mg/l) levels, respectively. Each treatment was replicated five times with six hens per replicate. Dietary inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The average amounts of triglyceride and total cholesterol in the yolk were reduced in the treatment group compared with the control. These results were similar to those of previous experiments utilizing l ‐carnitine or GABA in feed. Adabi et al and Kazemi‐Fard et al reported that l ‐carnitine reduced egg yolk cholesterol ( P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average amounts of triglyceride and total cholesterol in the yolk were reduced in the treatment group compared with the control. These results were similar to those of previous experiments utilizing l ‐carnitine or GABA in feed. Adabi et al and Kazemi‐Fard et al reported that l ‐carnitine reduced egg yolk cholesterol ( P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Adabi et al and Kazemi‐Fard et al reported that l ‐carnitine reduced egg yolk cholesterol ( P < 0.05). Oso et al demonstrated how l ‐carnitine reduced plasma lipid, total egg yolk cholesterol and triglyceride ( P < 0.05). It is possible that l ‐carnitine is associated with increased systemic breakdown of cholesteryl esters, increase in reverse cholesterol transport and excretion, and stabilization of a phospholipid‐based structure for very‐low‐density lipoprotein (VLDL) and low‐density lipoprotein (LDL) particles .…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, Al-Daraji and Tahir (2014) reported that dietary supplementation with L-carnitine (50, 100 and 150 mg kgG 1 diet) caused significant increases in egg fertility and hatchability and significantly decreased the embryonic mortality during incubation. Also, Oso et al (2014) found that dietary L-carnitine supplementation for turkey breeder hens produced the highest egg fertility and significantly reduced the late embryonic mortality. Such positive effects of dietary L-carnitine on hatchability of eggs might have been related to the increased egg fertility, the decreased late embryonic mortality and/or the prolonged incubation period.…”
Section: Resultsmentioning
confidence: 99%
“…However, Salmanzadeh et al (2013) found that injection of L-carnitine into eggs of turkey breeder hens on day 5 of incubation caused significant reductions in hatchability of fertilized eggs. On the other hand, dietary supplementation with L-carnitine has been reported to positively affect the hatchability of eggs (Oso et al, 2014;Al-Daraji and Tahir, 2014) while some investigators found no effect (Salmanzadeh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In avian species, it is special that the hen‐egg nutrient transfer is happened before the embryonic development. Actually, maternal dietary strategies can easily been used in birds to increase the performance and warfare of post‐hatch progeny (Zhao et al., ; Oso et al., ; Sun et al., ), as the nutrients composition of eggs is changeable with the hens' diet regimens (Botsoglou et al., ). Of particular interest is the application of maternal nutritional strategies to increase the antioxidant status and bone quality of progeny, which shows a potential to decrease the economic loss caused by oxidative stress and skeletal disorder.…”
Section: Introductionmentioning
confidence: 99%